Beyond the numbers : understanding the institutions for monitoring poverty reduction strategies - Bedi, Tara, 1978- (Washington, DC : World Bank, 2006)
Provides lessons on the design and functioning of monitoring systems which are based on the experiences of twelve countries that have implemented poverty reduction strategies. The book's focus is on the institutional arrangements of poverty reduction monitoring systems rather than on any particular activity or actor.
Includes bibliographical references (p. 223-230).
oif 19/08/15
Loan
Keywords: Poverty -- Government policy -- Developing countries -- Evaluation